Street smarts and critical theory : listening to the vernacular - McLaughlin, Thomas, 1948- (Wisconsin project on American writers., 1996)
Thomas McLaughlin argues that critical theory - raising serious, sustained questions about cultural practice and ideology - is practiced not only by an academic elite but also by savvy viewers of sitcoms and tv news, by Elvis fans and Trekkies, by labor organizers and school teachers, by the average person in the street.